2011
DOI: 10.2174/138161211798157766
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Abnormalities in Essential Hypertension

Abstract: Arterial hypertension is a very common disease and an important risk factor for cardiovascular disease. Patients with arterial hypertension are characterized by functional and structural vascular abnormalities. Vascular endothelium plays a fundamental role in modulating vascular tone and structure. The physiological production of the relaxing factors including nitric oxide, prostacyclin and hyperpolarizing relaxing factors protects the vessel wall by antagonizing the first pathogenetic steps of atherosclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
0
30
0
3
Order By: Relevance
“…30 In contrast, FMD reflects endothelial NO bioavailability, and increased arterial elasticity derived from increased endothelial NO bioavailability may increase BRS. 18 Chapleau et al reported that NO itself directly decreases baroreceptor activity, 31 whereas others reported that NO production in the brain increases BRS. 17 In addition, prostacyclin increases baroreceptor activity and oxygen free radicals decrease baroreceptor activity, 19,20 both being substances related to endothelial function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 In contrast, FMD reflects endothelial NO bioavailability, and increased arterial elasticity derived from increased endothelial NO bioavailability may increase BRS. 18 Chapleau et al reported that NO itself directly decreases baroreceptor activity, 31 whereas others reported that NO production in the brain increases BRS. 17 In addition, prostacyclin increases baroreceptor activity and oxygen free radicals decrease baroreceptor activity, 19,20 both being substances related to endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…9, 10 In contrast, FMD reflects the endothelial nitric oxide (NO) bio-availability, and NO directly contributes to baroreflex regulation in the brain, besides also contributing indirectly via its effect on arterial elasticity, which is a factor influencing barosensory vessel stretch. 17, 18 Furthermore, endothelial function-related substances such as prostacycline or oxygen free radicals may also directly modulate BRS. 19, 20 The significance of the association of AI/CBP or FMD with BRS, however, has not been fully clarified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, contractile activation and diameter of FAs were known to be under continuous control of SNA , a characteristic that could help reveal CNS-induced changes in SNA in hypertension. Finally, conduit arteries are of interest because they are importantly involved in the pathophysiology of hypertension, where increased conduit stiffness (possibly due to increased contractile activation) contributes to increased cardiac work (Sparks et al 2011;Sudano et al 2011).…”
Section: Rationale Of Use Of Fasmentioning
confidence: 99%
“…Thus, [Ca 2+ ] i in FA may reflect some of the systemic factors involved in altering diameter of the true resistance vessels, the small arteries and arterioles. Indeed, in human essential hypertension, conduit arteries such as FA are stiffer than normal, and this contributes to the pathology of hypertension, causing increased arterial pulse wave velocity and increased cardiac work (Sparks et al 2011;Sudano et al 2011).…”
Section: Introductionmentioning
confidence: 99%